MAKNA NILAI RELIGIUS TEMBANG MACAPAT MIJIL PADA PEMBELAJARAN SISWA SD - Qolbi, Lathifatul; Rohmaniah, Ajizatur; Ulfa, Fahmi Maria; Zulfahmi, Muhammad Nofan (Al-Wihdah: Jurnal Pendidikan Islam, 2024)
AbstractMacapat songs, one of Java's cultural heritage, have religious values that are relevant for elementary school students' learning. This article highlights the potential of Mijil songs as a medium for instilling religious values in character education. By using the literature study method and the Systematic Literature Review (SLR) approach, this research identifies the meaning and spiritual value of the Mijil song and its application in learning. The results of the study show that Mijil songs contain values and are closely related to Islamic religion, such as faith, honesty, hard work and responsibility which are important for forming students' character. Apart from that, this song can increase interest in learning through creative approaches, such as the use of interactive media. These findings reinforce the importance of integrating local wisdom in the curriculum to preserve culture while improving the quality of education. Keywords: Mijil Macapat Song, Religious Values, Elementary School Students. Abstrak Tembang macapat salah satu warisan budaya Jawa memiliki nilai-nilai religius yang relevan untuk pembelajaran siswa sekolah dasar. Artikel ini menyoroti potensi tembang Mijil sebagai media untuk menanamkan nilai-nilai religius dalam pendidikan karakter. Dengan menggunakan metode studi pustaka dan pendekatan Systematic Literature Review (SLR), penelitian ini mengidentifikasi makna dan nilai spiritual tembang Mijil serta penerapannya dalam pembelajaran. Hasil kajian menunjukkan bahwa tembang Mijil mengandung nilai-nilai dan berhubungan erat dengan reiligius Islam seperti keimanan, kejujuran, kerja keras, dan tanggung jawab yang penting untuk membentuk karakter siswa. Selain itu, tembang ini dapat meningkatkan minat belajar melalui pendekatan kreatif, seperti penggunaan media interaktif. Temuan ini memperkuat pentingnya integrasi kearifan lokal dalam kurikulum untuk melestarikan budaya sekaligus meningkatkan kualitas pendidikan. Kata kunci: Tembang Macapat Mijil, Nilai Religius, Siswa Sekolah Dasar.